Multiyear measurements of ebullitive methane flux from three subarctic lakes. Issue 3 (20th September 2013) - Wik, Martin; Crill, Patrick M.; Varner, Ruth K.; Bastviken, David
Abstract : [1] Ebullition (bubbling) from small lakes and ponds at high latitudes is an important yet unconstrained source of atmospheric methane (CH4 ). Small water bodies are most abundant in permanently frozen peatlands, and it is speculated that their emissions will increase as the permafrost thaws. We made 6806 measurements of CH4 ebullition during four consecutive summers using a total of 40 bubble traps that were systematically distributed across the depth zones of three lakes in a sporadic permafrost landscape in northernmost Sweden. We identified significant spatial and temporal variations in ebullition and observed a large spread in the bubbles' CH4 concentration, ranging from 0.04% to 98.6%. Ebullition followed lake temperatures, and releases were significantly larger during periods with decreasing atmospheric pressure. Although shallow zone ebullition dominated the seasonal bubble CH4 flux, we found a shift in the depth dependency towards higher fluxes from intermediate and deep zones in early fall. The average daily flux of 13.4 mg CH4 m −2 was lower than those measured in most other high‐latitude lakes. Locally, however, our study lakes are a substantial CH4 source; we estimate that 350 kg of CH4 is released via ebullition during summer (June–September), which is approximately 40% of total whole year emissions from the nearby peatland. In order to capture the large variability and to accurately scale lake CH4 ebullition temporally and spatially, frequent measurements over long time periods are critical. Key Points: Lake ebullition is a variable yet important source of atmospheric methane The water depth dependency of ebullition shifts over summer Frequent sampling over long time periods is critical to quantify ebullition